EUSATfinder: la soluzione spaziale e terrestre per la trasmissione dei dati in ambienti critici (GEOmedia, 2026)
The EUSATfinder project addresses the critical challenge of unreliable communications during emergency and rescue operations, particularly in remote or disaster-stricken areas.The solution is centered on the Mobile Operation Center (MOC), a deployable vehicle designed to manage a fleet of drones for in-situ data collection (images, videos, telemetry) and to act as a crucial communication gateway.EUSATfinder synergistically integrates European space assets: it utilizes Satellite Backhaul (SAT- COM), including priority GOVSATCOM services, for the secure transmission of data to remote control centers. It leverages Copernicus services (Rapid Mapping) for enhanced situational awareness. Furthermore, to ensure the secure navigation of Unmanned Aerial Vehicles (UAVs), the system implements Galileo OSNMA signal authentication and advanced GNSS Spoofing Detection (GSD) techniques based on AI.This system establishes a resilient and efficient model for modern disaster management and support for First Responders.